PARÂMETROS ASSOCIADOS À RESISTÊNCIA A Helicoverpa armigera (Lepidoptera: Noctuidae) DE GENÓTIPOS DE TOMATEIRO COM ALTOS TEORES DE ZINGIBERENO - Favaro Junior, Jorge Luis (2017)
The objective of this work was to evaluate a resistance of tomato genotypes with high levels of zingiberene, high densities of glandular trichomes in Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae). The evaluated genotypes were the commercial cultivar Redenção Solanum lycopersicum, with low content of zingiberene and low density of glandular trichomes, wild access Solanum habrochaites var. Hirsutum PI127826, with high content of zingiberene and high amounts of glandular trichomes, as well as four genotypes selected from the interspecific cross between them, RVTZ 2011079 117, RVTZ-2011-079-185, RVTZ-2011-079-335, RVTZ-2011-079-503. For the determination of the mechanisms of resistance, the zingiberene contents present in these genotypes and their possible variations in a 24 - hour shift and the amount of trichomes found in the leaves were analyzed. To verify the effects of antixose and antibiosis, the larvae were submitted to tests with and without a choice. The genotypes, Solanum habrochaites var. In the present study, it was found that the highest density of glandular trichomes were type IV and VI Levels of zingibereno. The form and the collection time did not interfere with the zingiberene levels in a 24-hour period. In the tests with no chance of choice, the H. armigera larvae exposed to genotypes of high zingiberene content and high density of mainly glandular type IV and VI trichomes presented lower displacement, lower values of survival, leaflet damage, and higher rejection in Tests with a chance of choice, when compared to the cultivar Redenção Solanum lycopersicum. From these tests it is possible to infer that the mechanism of the antibiosis and antioxenose type are involved in the resistance of these genotypes and that the higher density of glandular trichomes of type IV and VI are associated to the levels of zingiberene, negatively influencing the feeding, survival and displacement Of the larvae of Helicoverpa armigera, providing greater resistance to this pest.